LA CRISIS. PERSPECTIVAS DEL EMPLEO Y COMERCIO - Herrera García, Beatriz (2012)
In mid 2012, the developed economies are on the brink of a downward spiral driven by four mutually reinforcing factors: a sovereign debt crisis, a fragile banking industry, weak aggregate demand (associated with high unemployment), and paralytic policy frameworks caused by political and institutional weaknesses. These weaknesses are already a fact; however, a further deterioration in any of the m could trigger a vicious cycle leading to sever financial turmoil and a deepening economic crisis. This could also seriously affect emerging and other developing countries through trade and financial channels.